AB1206-HPR Adaptation into spanish of the scleroderma health assesment questionnaire (S-HAQ). (15th June 2017) - Quevedo, P; Rivero, MA; Perez, N; Laborde, H; Earsman, G; Mayer, M; Papasidero, S; Julia, S; Zaffarana, C; Maldonado, R; Khoury, M; Lara, M; et al.
Abstract : Background: The Health Assessment Questionnaire (HAQ) is an instrument administered to patients to self-report functional status originally in rheumatoid arthritis (RA). In Argentina, it has been translated and validated for RA in 2004. For diffuse SSc, HAQ has been associated to morbidity and mortality. Objectives: To adapt S-HAQ into Spanish and to assess its validity in SSc patients in Argentina. Methods: S-HAQ was translated following a forward-backward translation procedure of the original English version, and transcultural adaptation was performed by a comprehension test reaching the final Spanish version. SSc patients that fulfilled ACR 80 criteria and early Systemic Sclerosis according to Le Roy and Medsger criteria were included. Patients with overlap were excluded. Cronbach's alpha and item-item item-total correlations were used to assess internal consistency. Construction validity was analyzed through factor analysis with Varimax rotation. Continuous variables were compared by t-test, Mann-Whitney or Kruskal-Wallis test, and categorical variables by chi-square or Fisher's test. A value of p<0.05 was considered significant. Results: l9An adapted Argentine-Spanish version of S-HAQ was developed. One hundred patients were surveyed; 84% were female, mean age 54±12.8 years and disease duration 8.8±9.1 years. Limited SSc was more frequent (63%), followed by diffuse SSc (36%). Serologically, 89% were ANA positive, 27% had anti Scl 70 and 41% had anti centromere antibodies. Median Rodnan score (mRSS) was 9.8 (0–40.5) and median activity measured by EUSTAR was 1.25 (0–6). Median S-HAQ was 0.62 (0–2.5), Cronbach's alpha 0.89, and when removing questions one by one the coefficient decreased. Median VAS (visual analogue scale) was 0.57 (0–2.8). Factor analysis identified two factors for the S-HAQ: factor 1: dressing (0.61), arising (0.68), reach (0.63), and personal hygiene (0.70); factor 2: eating (0.68), grip (0.72), walking (0.49), usual activities (0.62). For questions, three factors were identified through VAS: factor 1: overall disease severity (0.63) and gastro-intestinal symptoms (0.57); factor 2: Raynaud's (0.66), digital ulcers (0.56); factor 3: respiratory symptoms (0.43). There was a statistically significant association between higher values of S-HAQ and higher values of mRSS (1.1±0.74 vs. 0.64±0.5 p=0.002) and also with seropositivity for anti-Scl 70 (p=0.003). Higher values of total VAS were associated to female gender (0.75±0.5 vs. 0.49±0.71, p=0.01). There was a significant association between S-HAQ and MEDSGER (p=0.04) and EUSTAR (p=0.03) scores; likewise, between VAS and MEDSGER (p=0.00) and EUSTAR (p=0.00) scores. Conclusions: A Spanish version of S-HAQ was developed, showing an acceptable reliability and validity. Disclosure of Interest: None declared